2021
DOI: 10.22495/jgrv10i1art10
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and firm performance in the emerging market: A review of the empirical literature

Abstract: After decades of many corporate scandals and financial meltdowns, the quest for effective corporate governance and firm performance has raised the concern of a lot of academicians, practitioners, and researchers regarding articles written on this issue. This study seeks to review corporate governance and firm performance articles written in Ghana under the author’s keywords in order to fulfill the objective. The goal is to identify the research trend and then to suggest the idea of future research directions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 92 publications
1
3
0
Order By: Relevance
“…Consequently, we agree with Antwi et al (2021) that independent directors should be selected from a wide range of different experiences and points of view. There are a lot of family businesses in developing countries, and many of them only allow family members to hold high management roles, which reduces the requirement of having independent board members.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consequently, we agree with Antwi et al (2021) that independent directors should be selected from a wide range of different experiences and points of view. There are a lot of family businesses in developing countries, and many of them only allow family members to hold high management roles, which reduces the requirement of having independent board members.…”
Section: Discussionsupporting
confidence: 82%
“…Accounting frauds are more likely to happen within a firm that has a poor governance structure, and this is especially true for organizations that are on the smaller side. The insufficiency of existing corporate governance legislation, principles, structures, and processes to prevent these types of frauds has stoked disputes over the effectiveness of these governing mechanisms ( Antwi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the changes are due in part to corporate scandals that began in the 1980s and late 1990s in the United Kingdom (UK), the United States of America (USA), and some Asian countries (Ahialey & Kang, 2019;Oliveira et al, 2012). According to Antwi et al (2021), CG has become a subject of discussion over the decades because of myriad corporate failures. Therefore, almost every country has established CG institutions, outlined best practices, and attempted to impose appropriate governance structures (Prusty, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent meta-analyses (e.g., Makkonen, 2022;Prashar and Gupta, 2021;Rhoades et al, 2000;Zubeltzu-Jaka et al, 2019) have highlighted the central role of board composition in corporate governance. Antwi et al (2021); Parente and Filho (2020) observed that a board of directors is one of the most studied constructs in corporate governance research as an antecedent of several important business outcomes. Six meta-analytic reviews show that gender, size, independence, and director status are some of the most commonly used indicators of board characteristics (Deutsch, 2016;Endrikat et al, 2020;Makkonen, 2022;Prashar and Gupta, 2021;Sierra-Morán et al, 2021;Zubeltzu-Jaka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%